Post-treatment of effluents from anaerobic reactors treating sewage by natural and non-natural coagulants. - Marcos Erick Rodrigues da Silva; Marisete Dantas de Aquino; André Bezerra dos Santos (Revista Tecnologia, 2009)
The current investigation aimed to study post-treatments for effluents of anaerobic sludge blanket reactors by using both natural (Moringa oleifera, Lam) and unnatural coagulants. For that, many jar-tests were conducted either using sewage or effluent of a lab-scale UASB (upflow anaerobic sludge blanket) reactor. Many dosages of natural (Moringa oleifera) and unnatural (ferric chloride) coagulants were tested with sewage. Afterwards, the coagulants effect associated to a polymer (FO 4140) was assessed in the physical-chemical and microbiological parameters of the UASB reactor effluent. The results indicated that the natural coagulant moringa provided low turbidity removal in comparison with the unnatural coagulant ferric chloride, for both sewage and UASB effluent, questioning the real application of moringa in the physical-chemical treatment of sewage. Additionally, a negative effect of the moringa seeds was verified after the detection of a considerably increase of the Chemical Oxygen Demand (COD) and turbidity, while testing the UASB effluent. The results show that, in general, the moringa seeds were inefficient on the removal of physical-chemical and microbiological contaminants present in sewage and anaerobic effluents.